2000
DOI: 10.1002/1097-0223(200009)20:9<750::aid-pd900>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and genetic analysis of double trisomy 48,XXX,+18

Abstract: Prenatal diagnosis of simultaneous occurrence of double trisomy involving chromosomes 18 and X is extremely rare. We report on the prenatal diagnosis, genetic analysis and clinical manifestations of a fetus with both trisomy 18 and trisomy X. A 26‐year‐old, para 1 woman was referred for genetic counselling at 36 weeks' gestation with the sonographic findings of intrauterine growth retardation (IUGR), polyhydramnios, ventricular septal defect, and an enlarged cisterna magna. Both cordocentesis and amniocentesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…One published pedigree even included siblings, one with DS and the other with the double aneuploidy 48,XXY+21 [14]. In families with trisomy 21 recurrence or double aneuploidy where the origin of non‐disjunction was investigated, the majority of cases were maternal [18,21,27–29], although a case of double aneuploidy with additional maternal and paternal chromosomes was also reported [30].…”
Section: Familial Aggregationmentioning
confidence: 99%
“…One published pedigree even included siblings, one with DS and the other with the double aneuploidy 48,XXY+21 [14]. In families with trisomy 21 recurrence or double aneuploidy where the origin of non‐disjunction was investigated, the majority of cases were maternal [18,21,27–29], although a case of double aneuploidy with additional maternal and paternal chromosomes was also reported [30].…”
Section: Familial Aggregationmentioning
confidence: 99%
“…Uchida and Bowman [1961] reported the first double trisomy case 48,XXX, + 18. Since then, a total of 16 cases have been reported [Ricci and Borgatti, 1963; Haas and Lewis, 1966; Engel et al, 1967; Taylor, 1968; Emberger et al, 1971; Madahar et al, 1974; Verma and Dosik, 1980; Rosenfeld et al, 1981; Sonoda et al, 1985; Imai et al, 1987; Sonoda et al, 1987; Jaruratanasirikul and Jinorose, 1994; Moore et al, 1994; Tsukahara et al, 1994; Chen et al, 2000]. One of the patients was a mosaic [Engel et al, 1967].…”
Section: To the Editormentioning
confidence: 99%
“…Whereas amongst first trimester miscarriages, 37 cases involving chromosome 21 and sex chromosomes have been reported . For chromosome 18 and sex chromosomes, a few live born cases have been reported (summarized in Chen et al .…”
Section: Summary Of Cases Of Double Aneuploidy Reported After First Tmentioning
confidence: 99%
“…Whereas amongst first trimester miscarriages, 37 cases involving chromosome 21 and sex chromosomes have been reported. 3 For chromosome 18 and sex chromosomes, a few live born cases have been reported (summarized in Chen et al 4 ), whereas among first trimester miscarriages, 34 cases have been reported. 3 Cases involving chromosome 13 and sex chromosomes appear to be rare with only seven cases amongst first trimester miscarriages.…”
mentioning
confidence: 99%